2004
DOI: 10.1300/j115v23n04_03
|View full text |Cite
|
Sign up to set email alerts
|

Educating Generation X and Generation Y

Abstract: This article provides a list of helpful teaching tips for instructional librarians who need to meet the changing generational needs of their patrons. Specific generational qualities and attitudes of Generation X and Generation Y are discussed along with educational techniques and software recommendations. These tips are based on the authors' experiences at Drexel University's Hahnemann Library and Thomas Jefferson University's Scott Memorial Library, both of which are academic health sciences libraries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 4 publications
0
9
0
1
Order By: Relevance
“…Bilinçli tüketim eğilimi ile X kuşağı arasında bulunan ilişki, yaş olarak X kuşağına mensup bireylerin daha olgun dönemlerinde olmasıyla da paralellik teşkil etmektedir. Literatürde benzer bir farklılık eğitim konusunda da tespit edilmiştir (Kipnis & Childs, 2004). Sürdürülebilir tüketim eğilimi ile ilgili ise aynı bağ kurulamamıştır.…”
Section: Tablo 4: Tüketici Karar Verme Tarzları öLçeği Faktör Dağılımıunclassified
“…Bilinçli tüketim eğilimi ile X kuşağı arasında bulunan ilişki, yaş olarak X kuşağına mensup bireylerin daha olgun dönemlerinde olmasıyla da paralellik teşkil etmektedir. Literatürde benzer bir farklılık eğitim konusunda da tespit edilmiştir (Kipnis & Childs, 2004). Sürdürülebilir tüketim eğilimi ile ilgili ise aynı bağ kurulamamıştır.…”
Section: Tablo 4: Tüketici Karar Verme Tarzları öLçeği Faktör Dağılımıunclassified
“…The more relaxed the environment, and the more socially conducive to discussions, the better will be the quality of the learning" (p. 31). Kipnis and Childs (2004) identified the key characteristics of Generation X and Y students that are useful in developing library training sessions. They concluded that the Generation Y students:…”
Section: The Millennial Generation and Educationmentioning
confidence: 99%
“…11 More than one author pointed out that, "cooperative teaching techniques have improved content learning, student achievement, and student self-esteem, which may explain why current students are comfortable collaborating on assignments." 12 Working in a group promotes learning amongst the students, learning from one another, and is less threatening of a task for students who may not perform when working alone.…”
Section: Student Generational Culturementioning
confidence: 99%
“…When we look at the capacity of the student," retaining 10% of read material, but 20 to 30% of what is seen," 12 we move from the verbal learner to a more visual learner. In addition, "documents that are text-based are not as popular as documents rich in images, including screen shots and step-by-step instructions."…”
Section: Student Generational Culturementioning
confidence: 99%
See 1 more Smart Citation